Incidence and outcomes of post‐transplant lymphoproliferative disease after 5365 solid‐organ transplants over a 20‐year period at two UK transplant centres. (2nd March 2022) - Santarsieri, Anna; Rudge, John F.; Amin, Irum; Gelson, Will; Parmar, Jasvir; Pettit, Stephen; Sharkey, Lisa; Uttenthal, Benjamin J.; Follows, George A.
Summary: Post‐transplant lymphoproliferative disease (PTLD) is a life‐threatening complication of solid‐organ transplantation (SOT). We present the incidence and outcomes of PTLD in a cohort of 5365 SOT recipients over a 20‐year period at two UK transplant centres. With a median follow‐up of 7.7 years, 142 of 5365 patients have developed PTLD. Cumulative incidence was 18% at five years after multivisceral transplant and 1%–3% at five years following the other SOT types. Twenty‐year cumulative incidence was 2%–3% following liver and heart transplantation and 10% following kidney transplantation. Median overall survival (OS) following SOT was 16 years, which is significantly reduced compared with the age‐adjusted UK population. There is relatively high early mortality following diagnosis of PTLD and only patients surviving two years regained a longer‐term survival approaching the non‐PTLD SOT cohort. Of 90 patients with monomorphic PTLD, diffuse large B‐cell lymphoma, 66 were treated with first‐line rituximab monotherapy and 24 received first‐line rituximab plus chemotherapy. Up‐front rituximab monotherapy does not appear to compromise OS, but the number of patients dying from non‐lymphoma causes before and after treatment remains high with both treatment approaches. Multivariate analysis of all 90 monomorphic PTLD patients identified an International Prognostic Index (IPI) of 3+ as the strongest pretreatment variable associating with inferior one‐year OS.